2004
DOI: 10.1007/bf03018421
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous lidocaine and ephedrine, but not propofol, suppress fentanyl-induced cough

Abstract: P Pu ur rp po os se e: : The aim of this study was to evaluate the effectiveness of lidocaine, propofol and ephedrine in suppressing fentanyl-induced cough.M Me et th ho od ds s: : One hundred and eighteen patients were randomly assigned into four groups and the following medications were given intravenously: patients in Group I (n = 31) received normal saline 2 mL, Group II (n = 29) received lidocaine 2 mg·kg and Group IV (n = 28) received ephedrine 5 mg. At one minute after the study medication, fentanyl 2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
119
6
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(131 citation statements)
references
References 18 publications
3
119
6
1
Order By: Relevance
“…Our study has shown that undiluted fentanyl, when administered through a peripheral venous line, provokes coughing in up to 32% of patients. Previous studies [1][2][3][4][5][6][7] have shown that the incidence of fentanyl-induced cough varies between 18% and 65%. In the study by Lin et al [1], 65% of the patients coughed following 2.5 lg.kg )1 fentanyl through a peripheral venous line within 2 s. A 46% incidence of cough has been reported with 7 lg.kg )1 fentanyl administered through a central venous catheter administered over 1 s by Bohrer et al [2].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study has shown that undiluted fentanyl, when administered through a peripheral venous line, provokes coughing in up to 32% of patients. Previous studies [1][2][3][4][5][6][7] have shown that the incidence of fentanyl-induced cough varies between 18% and 65%. In the study by Lin et al [1], 65% of the patients coughed following 2.5 lg.kg )1 fentanyl through a peripheral venous line within 2 s. A 46% incidence of cough has been reported with 7 lg.kg )1 fentanyl administered through a central venous catheter administered over 1 s by Bohrer et al [2].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [1][2][3][4][5][6][7] have shown that the incidence of fentanyl-induced cough varies between 18% and 65%. In the study by Lin et al [1], 65% of the patients coughed following 2.5 lg.kg )1 fentanyl through a peripheral venous line within 2 s. A 46% incidence of cough has been reported with 7 lg.kg )1 fentanyl administered through a central venous catheter administered over 1 s by Bohrer et al [2]. Another study by Lui et al [3] showed that 43% of patients coughed after receiving 5 lg.kg )1 fentanyl injected through a peripheral venous line over 5 s. Pandey et al [4] reported that 35% of patients coughed following 3 lg.kg )1 fentanyl given intravenously through a peripheral venous line.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fentanyl-induced cough could also be the result of a mechanical or chemical stimulation of sensory receptors within the respiratory tract; the afferent impulses from these receptors may activate a putative brainstem cough center [7]. Drugs such as ketamine, terbutaline, clonidine, dexamethasone, and lidocaine as well as performing some maneuvers such as a forced expiration against open glottis, dilution of fentanyl to 10 μg/ ml, and prolonged injection time have all been evaluated in reducing this fentanyl induced cough [8][9][10][11][12][13]. Dextromethorphan is an antitussive drug that is used for suppression of cough caused by minor throat and tracheo-bronchial irritation, especially after inhalation of any irritants.…”
Section: Introductionmentioning
confidence: 99%